Specifics of Sex Life and Methods of Birth Control Among Students at the University of Osijek : Osobitosti spolnog života i metode kontracepcije među studentima Sveučilišta u Osijeku - Bosnić, Zvonimir (Array, 2021)
The aim of this study is to define specifics of sex life and methods of birth control among students at the University of Osijek. Participants were students who study at Josip Juraj Strossmayer University of Osijek. A newly formed questionnaire containing 31 questions was used for this purpose. The study included 549 voluntarily students, 54.3% of students had first sexual experience between 16 and 18 years of age. Most of them were long-term couples, who are managing better with sexual activities then students in short-term relationships, who are more stressed because of their studies. When it comes to the type of contraceptives, 71, 9 % of students used some of birth control methods, and most common is condom (75.9 %). However, 27. 9 % of students believe that natural methods of birth are safe enough. There are no significant differences in age at the time of first sexual activity considering gender, year at university and residency. The biggest reason for not using contraception is long-term relationship in which students do not feel fear of sexually transmitted diseases and pregnancy.